The Impact of Financial Inclusion and Digitalizationon Income ‎Inequality: A Panel Data Analysisfor ASEAN - Camba Jr.‎ , Abraham C. (International Journal of Accounting and Economics Studies, 2026)
This study examines the impact of financial inclusion and digitalization on income inequality in selected ASEAN countries over the period ‎‎2011–2024 using panel data econometric techniques. Fixed Effects (FEM), Random Effects (REM), and Generalized Method of Moments ‎‎(GMM) estimators are employed to capture both static and dynamic relationships while accounting for unobserved heterogeneity and potential endogeneity. Correlation analysis indicates that financial inclusion and digitalization are moderately associated with lower income equality. FEM results show that financial inclusion significantly reduces inequality, whereas digitalization initially increases inequality, suggesting uneven distributional benefits during the early stages of digital adoption. These mixed results reflect transitional digital divide im-‎pacts in early digitalization phases, where access and digital capabilities remain uneven. In contrast, REM and GMM estimates reveal that ‎digitalization has a statistically significant inequality-reducing impact, highlighting its broader and dynamic role in expanding access to digital finance, employment opportunities, and entrepreneurial activity. Financial inclusion remains statistically insignificant in these models, ‎indicating that its short-run distributional impact may be limited without inclusive outreach and effective utilization. Overall, the findings ‎suggest that while digitalization contributes to inequality reduction over time, financial inclusion requires targeted and complementary poli‎cies to generate sustained distributive effects. The results provide relevant policy implications for promoting inclusive growth in ASEAN ‎economies‎.